العدالة عند جان رولز (Comprehensive Journal of Science, 2026)
This study examines the development of the concept of justice in philosophical thought from ancient times to contemporary political philosophy, with a particular focus on John Rawls’s theory of justice. It presents the views of justice in Plato as social and moral harmony, and in Aristotle as giving each his due within a practical legal framework. It then moves to modern philosophy, which associated justice with authority and order in Hobbes, the protection of natural rights in Locke, the general will in Rousseau, and the universal moral law and respect for human dignity in Kant.Within this historical and intellectual context, John Rawls emerges as one of the most influential philosophers of the twentieth century, as he reformulated the concept of justice through his theory of “justice as fairness,” rejecting utilitarian approaches that allow the sacrifice of minority rights in the name of overall social benefit. Rawls grounded his theory in the concepts of the “original position” and the “veil of ignorance” to ensure the neutrality of social rules, and articulated two fundamental principles of justice: the principle of equal basic liberties and the difference principle, which permits social and economic inequalities only insofar as they benefit the least advantaged members of society.The study also offers a critical comparison between Rawls’s theory and utilitarianism, classical liberalism, Marxism, and libertarianism, highlighting its strengths—particularly its balance between individual freedom and social equality and its concern for marginalized groups—alongside its limitations, such as its idealistic nature and the difficulties of applying it in complex political realities, especially under conditions of globalization and cultural pluralism. The study concludes that Rawls’s theory represents a significant contribution to the understanding of social justice and provides an important moral and legal framework, yet it requires adaptation and further development to suit different contexts, particularly in non-liberal societies and the Arab world.
Keywords: Justice, Political Philosophy, John Rawls, Justice as Fairness, Original Position, Veil of Ignorance, Freedom, Equality, Difference Principle, Utilitarianism